2020
DOI: 10.1167/tvst.9.6.24
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol-Based Synthetic Hydrogel Sealant for Filtration Bleb Leaks: An In Vivo and Histologic Study

Abstract: To evaluate the efficacy of polyethylene glycol (PEG)-based synthetic sealant for closing bleb leaks after glaucoma filtration surgery. Methods: Tube shunt surgery that included implantation of a 22-gauge indwelling catheter and intraoperative mitomycin C was performed in the left eyes of 11 New Zealand white rabbits. Seven days postoperatively, all filtration blebs were perforated with an 18-gauge needle to create a bleb hole. In six rabbits, the holes were covered with the sealant and irradiated with blue-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…85 PEG is commonly used as a sealant to prevent leakage of liquid and air after surgery. 86,87 At present, the development of synthetic chemical adhesives mostly involves the modification of existing medical polymeric materials and combining them with different chemical substances to make them have more abundant functionalities. 88 However, when compared to existing chemical polymeric materials, biomaterial-derived materials have better properties and are suitable for application in biomedicine.…”
Section: Organic Synthetic Adhesive Materialsmentioning
confidence: 99%
“…85 PEG is commonly used as a sealant to prevent leakage of liquid and air after surgery. 86,87 At present, the development of synthetic chemical adhesives mostly involves the modification of existing medical polymeric materials and combining them with different chemical substances to make them have more abundant functionalities. 88 However, when compared to existing chemical polymeric materials, biomaterial-derived materials have better properties and are suitable for application in biomedicine.…”
Section: Organic Synthetic Adhesive Materialsmentioning
confidence: 99%
“…The majority of authors used hydrogels as a drug delivery system: they are implanted and provide for a localized and prolonged release of the drug they contain. Nagata et al [ 155 ], Xi et al [ 156 ], and Kojima et al [ 157 ] studied MMC-loaded hydrogels. They demonstrated that hydrogel causes a prolonged and controlled release of MMC, reducing its toxicity while simultaneously reducing the formation of fibrosis and ensuring a prolonged persistence of the bleb.…”
Section: Hydrogel Formulation After Glaucoma Surgerymentioning
confidence: 99%
“…The leakage occurrence as a short-term complication after glaucoma surgery is becoming more frequent because of the increased application of mitomycin-C to delay wound healing [ 175 ]. Nagata et al proposed a PEG-Based Synthetic Hydrogel as a sealant after glaucoma surgery to inhibit bleb leaking [ 155 ]. On a rabbit model, they observed fewer lymphocytic infiltrations without inflammatory effects or conjunctival toxicity [ 155 ].…”
Section: Hydrogel Formulation After Glaucoma Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…( Osbun et al, 2012 ) In addition, in the field of ophthalmology, the PEG-based synthetic sealant could also act as an adhesion barrier to prevent leakage of filtration blebs and as an adhesive to close sclerotomies of PPV in rabbit eyes. ( Hoshi et al, 2016 ; Nagata et al, 2020 ).…”
Section: Sealants Of Synthetic Materialsmentioning
confidence: 99%